A hybrid time and frequency domain digital implementation of flickermeter based on mirror image extension. Issue 7 (12th March 2019) - Wu, Xiaodong; Tian, Muqin; Zhu, Yanfang; Zhao, Qiaoe; Liu, Fang
Abstract : The flickers caused by wind farm should be assessed accurately because they become a limiting factor for integrating wind turbines into a grid. The traditional flickermeter uses the fast Fourier transform (FFT), weighting in the frequency domain, and the inverse FFT process to weight the flickers to simulate the eye‐brain sensitivity to the lamp illumination behavior. However, because of the lower frequency resolution, spectral leakage will occur when the flickers transform into the frequency domain via FFT, then it may cause runaways in both ends of the weighted flickers and the runaways are more serious in the low‐frequency band, finally the assessment accuracy cannot meet the design criteria required by IEC Standard 61000‐4‐15 because the flicker frequencies of wind farm are in the low‐frequency band. An improved digital flickermeter implementation in the hybrid time and frequency domain is proposed in this article. Simulations and actual measurements show that the mirror image extension can improve the runaway through changing the phase angle of the flicker equivalently to make the results more accurate in the low‐frequency band when the frequency resolution decreases. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.